Fungal sporulation in a Permian plant fragment from Antarctica. Bulletin of Geosciences - Harper, Carla (My University, 2018)
Documented evidence of fungi from the Permian of Antarctica mostly consists of dispersed remains that do not provide the whole complement of diagnostic features necessary to determine even broad systematic affinities. A dense cluster of> 250 fungal spores occurs within a degraded vascular plant (probably glossopteridalean) fragment in Permianpermineralized peat from Skaar Ridge, central Transantarctic Mountains, Antarctica. Spores are spheroidal to ovoid,~ 50 μm in diameter, and possess a massive wall composed of three wall components (wc1–3); one or two canals extend from the spore lumen to the outside. The spores are embedded in a confluent meshwork of tenuous hyphae. Structural similarities exist between the fossil spores and spores produced by certain present-day Mucoromycota, Ascomycota, and Basidiomycota; however, the precise systematic affinities of the fossils cannot be determined. The relationship between the spore producer and its also host plant remains unresolved. Nevertheless, the spatial arrangement of the spores within the plant structure suggests that the fungus required the host for sporulation, and perhaps even influenced plant development for this purpose. This discovery adds to the inventory of distinctive fungal fossils from the Permian of Antarctica and presents a new type of association/interaction between a Permian fungus and a vascular plant.
PUBLISHED
Keywords: Development; Interaction; Glossopteris; Parasitism; Saprotrophism; Spore wall; Smart & Sustainable Planet; ANTARCTICA; FOSSIL; FUNGI; Fossil Fungi; Fossil spores; Fossils; MICROFUNGI; PERMIAN